2021
DOI: 10.46827/ejfl.v5i3.3527
|View full text |Cite
|
Sign up to set email alerts
|

Receptive Vocabulary Knowledge of University Students in Clil Instruction

Abstract: Content and Language Integrated Learning (CLIL) has recently attracted the attention of practitioners in the language teaching field. As the name suggests, CLIL is an approach built upon teaching content-based area through a language as a medium. For such a language learning process, one of the important language aspects is vocabulary. The number of words language learners know - vocabulary size - and how well they know those words - vocabulary depth - (overall, the receptive dimension of word knowledge) are c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…CLIL has been adopted worldwide as a successful teaching approach that promotes more motivated and sustained learning attainment (Marsh, 2000). A wealth of studies adopting CLIL principles have been conducted (e.g., Fan & Lo, 2016;Fazzi & Lasagabaster, 2021;Kalay, 2021;Navarro-Guzman et al, 2021;Mahan, 2020;Pérez Cañado, 2020;Thuy & Nguyen, 2016;Yang, 2015).These previous CLIL empirical studies have congruently demonstrated its positive impacts on encouraging students to concurrently learn the content subjects and the target language across disciplines (e.g., psychology, engineering, physical education, mathematics), at a number of educational establishments (e.g., high schools, vocational colleges, universities), in different levels of the educational paradigm (i.e., young learners, teenagers, and adults), and in a variety of academic contexts and linguistic backgrounds (e.g., Taiwan, Vietnam, and many European countries).…”
Section: Introductionmentioning
confidence: 99%
“…CLIL has been adopted worldwide as a successful teaching approach that promotes more motivated and sustained learning attainment (Marsh, 2000). A wealth of studies adopting CLIL principles have been conducted (e.g., Fan & Lo, 2016;Fazzi & Lasagabaster, 2021;Kalay, 2021;Navarro-Guzman et al, 2021;Mahan, 2020;Pérez Cañado, 2020;Thuy & Nguyen, 2016;Yang, 2015).These previous CLIL empirical studies have congruently demonstrated its positive impacts on encouraging students to concurrently learn the content subjects and the target language across disciplines (e.g., psychology, engineering, physical education, mathematics), at a number of educational establishments (e.g., high schools, vocational colleges, universities), in different levels of the educational paradigm (i.e., young learners, teenagers, and adults), and in a variety of academic contexts and linguistic backgrounds (e.g., Taiwan, Vietnam, and many European countries).…”
Section: Introductionmentioning
confidence: 99%
“…Researchers nowadays have a prominent interest in vocabulary knowledge. Therefore, literature shows that some of them link this topic to the four skills of the language learning, listening, reading, writing, and speaking, and some of them link the topic to other linguistic aspects (Luo, Wan, & Zhang, 2021;Namaziandost, Kumar, & Çakmak, 2021;Wero, Machmud, & Husain, 2021;Kalay, 2021;Ha, 2021;Enayat & Derakhshan, 2021).…”
Section: Introductionmentioning
confidence: 99%